1988
DOI: 10.1128/jcm.26.7.1349-1352.1988
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and identification of pathogenic mycobacteria by combining radiometric and nucleic acid probe methods

Abstract: The combination of radiometric methodology (BACTEC 12B) and probe technology for recovery and identification of mycobacteria was studied in two large hospital laboratories. The sediment from vials with positive growth indices was tested with DNA probes specific for Mycobacterium tuberculosis, Mycobacterium avium, and Mycobacterium intracellulare. The sensitivity of the radiometric method and the specificity of the probes resulted in a marked reduction in the time to the final report. Biochemical testing could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The identification of clinically significant mycobacteria can be achieved within a few hours, once sufficient growth is available, using nonradioactively labelled DNA probes (134,178,304,383,425). Positive broth cultures can be concentrated by centrifugation and directly tested with the probes; some investigators believe the results should be confirmed by testing organisms isolated on solid media (142,380). The DNA probe tests are considered highly specific and sensitive.…”
Section: Laboratory Diagnosis Isolation and Identificationmentioning
confidence: 99%
“…The identification of clinically significant mycobacteria can be achieved within a few hours, once sufficient growth is available, using nonradioactively labelled DNA probes (134,178,304,383,425). Positive broth cultures can be concentrated by centrifugation and directly tested with the probes; some investigators believe the results should be confirmed by testing organisms isolated on solid media (142,380). The DNA probe tests are considered highly specific and sensitive.…”
Section: Laboratory Diagnosis Isolation and Identificationmentioning
confidence: 99%
“…For example, culture-positive broth from the BACTEC bottle has been concentrated by centrifugation and the pellet has been used as a source of organisms for identification by the Gen-Probe TB DNA probe. Organisms were usually detected and identified within 2 weeks of culture inoculation (109,110). Approximately 75% of state public health laboratories now use a combination of nucleic acid probes, HPLC, and the NAP test for rapid identification of M. tuberculosis in culture (154).…”
Section: Conventional Laboratory Methods For Diagnosingmentioning
confidence: 99%
“…The dorsal surface of the tongue is the most common oral site, followed by the palate, gingiva, buccal mucosa, and lips. Tuberculosis of the cervical lymph nodes is called scrofula and may result in breakdown of the skin overlying the nodes and fistula formation (41,44,45,83,127,131,139). Primary oral mucosal infection with the tubercle bacillus has been reported in patients treated by a dentist with active tuberculosis after the dentist performed dental extractions.…”
Section: Mycobacterial Infectionsmentioning
confidence: 99%
“…Mycobacterial culture of the organism from sputum is the most reliable means of diagnosis; however, 6-12 weeks is required to isolate and identify the organism. Recent developments in rapid detection and identification are reducing laboratory time (44,114,131).…”
Section: Mycobacterial Infectionsmentioning
confidence: 99%